Dimensi Psikologi Komunikasi dalam Dakwah Umar Bin Khattab Pada Pidato Pertama Menjadi Khalifah - Wahyuni, Sri; Mawasti, Wahanani (STID Al-Hadid, 2025)
THE PSYCHOLOGICAL DIMENSION OF COMMUNICATION IN UMAR BIN KHATTAB'S DA'WAH IN HIS FIRST SPEECH AS CALIPH. This study aims to examine the psychological dimensions of communication in Umar bin Khattab’s inaugural address upon his appointment as Caliph in 13 AH. Within the context of da’wah leadership, communication between leaders and followers plays a pivotal role. Effective da’wah communication requires consideration of the communicants’ psychological aspects to foster a positive impression among members, ensure message acceptance, encourage engagement, achieve communication objectives, and avoid coercive tendencies. This research employs a qualitative descriptive approach, utilizing a literature review and rational analysis to explore the psychological dimensions embedded in Umar bin Khattab’s speech. The findings reveal that Umar bin Khattab demonstrated a profound awareness of psychological communication principles in his first address as Caliph. His approach effectively responded to the community’s concerns regarding leadership transition and succeeded in restoring collective confidence and emotional stability. The psychological dimensions identified in his speech include systematic message organization, structured argumentation employing a pros-and-cons pattern, and message content that integrates both rational and emotional appeals.